2021
DOI: 10.1017/s0021859621001015
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical and preservative potential of Acacia mearnsii and Acacia dealbata leaves for ruminant production and product quality enhancement

Abstract: Seasonality and species are key aspects of the abiotic and biotic environment, respectively, that influence nutrient, phytochemical and antioxidant profiles of invasive alien plants leaf-meals. The current study investigated the effects of season on nutrient, amino acid, fatty acid, mineral, bioactive polyphenolic composition and antioxidant activity of Acacia mearnsii and A. dealbata leaf-meals. Overall, A. mearnsii leaf-meal harvested in the hot-dry-season had greater crude protein, ether extract, neutral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 103 publications
(143 reference statements)
1
5
0
Order By: Relevance
“…Recently, an interesting investigation on the seasonality effects of Acacia spp. on nutrient content, polyphenols and antioxidant activity showed that A. mearnsii had a nutritional and nutraceutical value higher than that of A. dealbata leaf-meals [87]. This finding was in line with a previous report on the ability of Acacia mearnsii to positively impact animal production, showing an effect on methanogenesis when used at the level of 30 g/kg (equivalent to 15 g total tannin/kg as analysed) [88].…”
Section: Effect Of Polyphenols On Rumen Fermentation Parameterssupporting
confidence: 90%
“…Recently, an interesting investigation on the seasonality effects of Acacia spp. on nutrient content, polyphenols and antioxidant activity showed that A. mearnsii had a nutritional and nutraceutical value higher than that of A. dealbata leaf-meals [87]. This finding was in line with a previous report on the ability of Acacia mearnsii to positively impact animal production, showing an effect on methanogenesis when used at the level of 30 g/kg (equivalent to 15 g total tannin/kg as analysed) [88].…”
Section: Effect Of Polyphenols On Rumen Fermentation Parameterssupporting
confidence: 90%
“…A signi cant drop in nutritive value, particularly crude protein (CP) from about 12% in the wet season to as low as < 2% in the dry season (Mapiye et al, 2009;Moyo et al, 2012) result in drastic shortfalls in meeting the protein requirements for both maintenance and production of sheep (NRC, 2007). In addition, the proliferation of invasive alien plants (IAPs), especially Australian Acacias (i.e., Acacia dealbata and A. mearnsii) has reduced rangeland production (Yapi et al, 2018;Gouws and Shackleton, 2019) and impacted negatively on livestock health, meat production and quality (Dezah et al, 2021;Uushona et al, 2021). Invasive Acacias are currently harvested by local communities for timber and fuelwood, and this often yields by-products such as leaves and bark, which currently have limited local value.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive Acacias are currently harvested by local communities for timber and fuelwood, and this often yields by-products such as leaves and bark, which currently have limited local value. Strategies are being developed in the tropics to increase the economic value of invasive Acacias' leaves and bark to local communities, including their use as livestock feed and meat preservatives because they contain moderate to high levels of nutrients and polyphenols (Dezah et al, 2021;Uushona et al, 2021;2022).…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Although A. mearnsii wood is used for producing several products, signicant amounts of A. mearnsii leaves are typically discarded due to the lack of suitable processing methods, causing huge waste production and the proliferation of pests and diseases. 8 Hence, developing strategies to utilize A. mearnsii leaves is important for economic as well as environmental benets.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, A. mearnsii leaves were found to have anti-inammatory, 12 anti-bloat, antioxidant and antimicrobial properties. 8 Flavonoids are important polyphenols consisting of two benzene rings linked by a heterocyclic six-membered pyrone ring (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%